Contribution à l’étude physiologique et Anatomique de l’espèce Atriplex halimus et Atriplex canescence cas Mostaganem et Oran - BANOUH, Kamal (My University, 2018)
This study consists in carrying out a preliminary evaluation of the physiological and Anatomical properties of two species of Atriplex, Atriplex halimus L which are a spontaneous indigenous polymorphic species in Mostaganem and Atriplex canescens, a species introduced (exotic) in Algeria for a long time within the framework of the fixing of the dunes and the readjustment of the degraded grounds taken with the Lake Télamine Oran. The results show that the witness presents a germination which starts after two days with a rate of 20% and a maximum value of the germination rate 100% is reached the fifth day. regarding to the action of 15°C temperature on the germination of seeds of Atriplex halimus it marks a rate of 33, 33% the third day, and reached a maximum value of 100% at the end of five days. We noticed a delay of two days in the germination of this species. The temperature of 20 ° C seems to have the same affect as the previous temperature, with 30°C we noticed an absence of germination during five days thus a delay, with the sixth days, the rate of germination is 16.67%. For Atriplex canescence the results shows that the witness presents a delay of three days. The highest rate 70% was noticed the eighth day of germination. The effect of the temperature of 15 °C brand a rate of maximum germination of 60% recorded at the end of five days. We noticed also a delay in the two days of germination. To 20 °C the highest rate of germination is 40% is recorded the third day, No germination was observed beyond the third day and 30 °C a rate of maximum germination is 20% at the after five days, and a delay of germination is four days. Atriplex halimus on the other hand presents a higher coefficient of swiftness (17,33%) to a room temperature witnesses the least low is that of seeds germinated at a temperature of 30 C° (14.28%). We recorded an average time of seven days of germination for the treatment of 30C temperature. On the other hand for Atriplex canescence the highest coefficient of swiftness is that of seeds germinated at a temperature of 20 C° (18,18%) and the least low of seeds germinated at the temperature of 30 C° (15.38%) is that. The average time of germination least low is that of seeds germinatedat atemperatureof15 C° (5days). The anatomy of Atriplex halimus presents descellules épidermiquesétroitementjuxtaposées with their variable geometrical forms. The globulous round blisters of form their colors is transparent. An aquiferous parenchyma which is of reserve. A lacunary parenchyma. The anatomy of latige one distinguishes in the center from the cut one notices a formed medullary parenchyma by bulky, isodiametric or lengthened cells, for the Sheet the 'higher skin is made up desplusieursassises cellulairesprotégé by a layer of cell which forms the cuticle and a small island of cell of fabrics of support collenchyme, the sclérenchyme form a sheath which surrounds conducting fabrics. The trichomes which formentsur higher skin of the blisters blanchâtres of forms well développéesglobuleuseset of a great density. Anatomy of Atriplexcanescence present of the épidermiques of form very developed and bulky and a chlorophyllian parenchyma, well developed stomata and many cells, Unegaine of large-sized chlorenquimatic cells which surround vascular fabrics. Quite distinct Elleest at this species (standard Kranz). The anatomy of the Stem presents unparenchyme medullary very developed with cells of great form. The skin consists of several layer of round cells, the parenchyma cortical is less present, the sclérenchyme form a sheath contained (a circle). The Sheet presents unecuticule made of only one lay down cell. Épidermeconstitué by quelquesassises cellular. One observes also the chlorophyllian and lacunary parenchyma which is characterized by cells more or less round or spangled, but the majority is spangled. The trichomes which one the shape of blisters filled with water with a crystal aspect, only one can say that these blisters are less dense on the surface and of small taille.la colouring in neutral red towards a type quite distinct from blisters directs us what one bulbous appelletrichomes which is smaller. These bulbous trichomes are fewer one finds them scattered on all the surface of the sheet.
Keywords: Atriplex halimus; Atriplex canescence; température; vitesse de germination; anatomie tiges; feuilles; trichomes; temperature; speed of germination; anatomy stems; sheets; trichomes